Revision of Wenyonia Woodland, 1923 (Cestoda: Caryophyllidea) from catfishes (Siluriformes) in Africa - Schaeffner, Bjoern C; Jirků, Miloslav; Mahmoud, Zuheir N; Scholz, Tomáš (Systematic parasitology, 2011)
Tapeworms of the genus Wenyonia Woodland, 1923 (Caryophyllidea: Caryophyllaeidae), parasites of catfishes in Africa, are revised. This revision is based on material from large-scale sampling, in the Democratic Republic of the Congo, Kenya, Senegal and the Sudan between 2006 and 2009, and the examination of all of the type-specimens available. The following six species are considered valid and their redescriptions are provided: Wenyonia virilis Woodland, 1923 (type-species; new synonym W. kainjii Ukoli, 1972); W. acuminata Woodland, 1923; W. longicauda Woodland, 1937; W. minuta Woodland, 1923 (new synonym W. mcconnelli Ukoli, 1972); W. synodontis Ukoli, 1972; and W. youdeoweii Ukoli, 1972. A key to the identification of Wenyonia spp. is provided and numerous new hosts and geographical records are reported. A comparative phylogenetic analysis of partial sequences of the 28S rRNA gene of four species divided the monophyletic genus into two lineages, one represented by W. acuminata and W. minuta and another one composed of W. virilis and W. youdeoweii.
Keywords: Cestoda; DNA helmintů; DNA, Helminth; Cluster Analysis; fylogeneze; Sequence Analysis, DNA; Phylogeny; ribozomální DNA; sekvenční analýza DNA; Afrika; shluková analýza; molekulární sekvence - údaje; Microscopy; mezerníky ribozomální DNA; Catfishes; RNA ribozomální 28S; Animals; Africa; mikroskopie; zvířata; DNA, Ribosomal Spacer; Molecular Sequence Data; DNA, Ribosomal; sumci; RNA, Ribosomal, 28S